Redes comerciais entre Itália e a Península Ibérica: fretes marítimos da Companhia Nerone-Salviati, 1454-1461 - Ana Clarinda Cardoso (Ler História, 2020)
The Nerone-Salviati commercial company (1454-1464), based in Pisa, specialized its relations with the Iberian Peninsula, namely with Barcelona, ​​Tortosa, Valencia and Lisbon. Using the company records, we will focus our study on the set of maritime freights between the Iberian area and Tuscany; in an articulated analysis of the agents involved, the commodities transported back and forth, the type of ships, the routes, and the seaports. Our main objectives are to understand how naval logistics were structured, how they intersected with the commercial network in the Iberian Peninsula, and to identify the preferred port structures. It is also intended to understand if there was a relationship between the commodities transported and the type of vessel, trying to gauge the role of the Portuguese maritime fleet in the range of freights hired by the company Nerone-Salviati.